Follow-up care in patient with breast cancer and myeloradiculopathy with severe care dependency: A case report - Arina Elhaqqa; Nursiswati (The Journal of Palembang Nursing Studies, 2024)
Background: Breast cancer stands as the most prevalent form of cancer worldwide. Metastasis to the bones represents the third most frequent occurrence in breast cancer, potentially leading to radiculopathy due to the presence of lesions. Consequently, in patients with breast cancer and myeloradiculopathy experiencing medical complications, it becomes imperative to conduct follow-up care. Such care aims to assess the treatment regimen’s effectiveness, offer motivation to patients, and impart education to both patients and their family caregivers.Objective: To assess the evolving levels of care dependency in complex breast cancer patients, employing a case report methodology.Case: This study provides an analysis of patient dependency levels seven days prior (a0) and during follow-up care, one month post laminectomy (a1), aiming to compare dependency changes in individuals diagnosed with breast cancer accompanied by myeloradiculopathy before and after laminectomy. The methodology adopted involves a case report focusing on a single patient diagnosed with breast cancer and myeloradiculopathy, assessing dependency levels using the barthel index and care dependency scale. Results revealed notable differences in the dependency levels observed one week before and one month after the laminectomy procedure. Conclusion: This report indicates that the patient’s dependency level aligns with limited mobility and an inability to maintain personal hygiene independently. The findings underscore the necessity for comprehensive nursing follow-up care.